Investigate the Effect of Dust, Air Velocity and Temperature on Photovoltaic Cells Performance - Jabari, Huda; Azzeh, Mohammed; khalefha, Mohammed (My University, 2016)
Nowadays, the energy becoming the main driver of the progress of civilization and a key element in human life, but the depletion of fossil fuel which is the primary source of this energy, which is one of non-renewable sources While the world is suffering from climate change and pollution of its air and the risk of decline in the Ozone layer, has become a challenge that the world faces how to find alternatives to energy-friendly environment. The main idea of the project to study the effect of natural conditions on the photovoltaic module (temperature, dust and air velocity) through laboratory experiments (indoor experiments), in order to reach the best efficiency is to obtain the highest value of electrical power generated from PV module. This project investigates the environmental effects (Temperature, Dust and air velocity) on the photovoltaic module (mono-crystalline) performance. The degradation of PV performance due to the increase of temperature, dust density and air velocity has been investigated. A series of experiments were conducted in order to study the effect of these parameters on the PV performance. In the first section, the effect of temperature on the I-V curve, Power, and efficiency was explained. In the second section, the effects of several type of dust were studied. These are red soil, sand and calcium carbonate. The experimental results show that the PV voltage and power is strongly depends on pollutant type and deposition level. also in third section which talking about the effect of air velocity on PV performance, and how the increasing in the air velocity affects the PV efficiency, more heat can removed from the PV module surface and higher air velocity decrease the relative humidity which lead to better PV efficiency. الملخص في عصر أصبحت فيه الطاقة بمصادرها المختلفة هي المحرك االساسي للتقدم الحضاري وعنص ار أساسيا في حياة البشر، وفي ظل تناقص كميات النفط األحفوري الذي يعتبر المصدر األساسي لهذه الطاقة والذي يعتبر من المصادر الغير متجددة وفي حين يعاني العالم من التغير المناخي وتلوث هوائه وخطر انحسار طبقة األوزون وارتفاع معدالت الح اررة، أصبح التحدي الذي يواجه العالم كيفية أيجاد بدائل للطاقة صديقة للبيئة بحيث تحد من استنزاف مصادر الطاقة الغير متجددة وتسعى إلى توصيل الطاقة إلى مختلف أرجاء العالم دون المساس بالبيئة وبأسعار مقبولة. يوجد هناك العديد من المؤثرات على الخاليا الشمسية الطبيعية منها والصناعية والتي تؤدي الى تقليل من كفاءة الخاليا الشمسية وتعتبر المؤثرات الطبيعية من أ هم العوامل التي يلزم مراعاتها عند تصميم مشاريع الطاقة الشمسية . والقصـور فـي مراعاة العوامل المناخية قد يؤدي إلى سوء تشغيل هذه المنظومة وضعف االستفادة من الطاقة المتاحة منها. تقوم الفكرة الرئيسة للمشروع على دراسة تأثير الظروف الطبيعية على الخاليا الشمسية )الغبار, الحرارة ,الرياح ,االشعاع الشمسي ( من خالل تجارب مخبرية بهدف التوصل الى افضل كفاءة تتمثل بالحصول على اعلى قيمة للقدرة الكهربائية الناتجة من للخاليا الشمسية باالضافة للوصل الى نسبة تاثير كل نوع من انواع المؤثرات الطبيعية على القدرة الناتجة والتوصل لمعامل لكل نوع من انواع المؤثرات.
no of pages 145, طاقة 5/2016
Keywords: Effect of Dust; Air Velocity; Temperature on Photovoltaic; Cells Performance